Person Re-Identification Using CNN Method With Combination of SVM and Semantic Segmentation - Kurniawan, Kristian Adhi; Soeleman, Moch Arief (LPPM Universitas Dian Nuswantoro, 2024)
Abstract – Person re-identification is a mechanized procedure of video investigation which has been widely studied in contemporary years. Research problems that are often raised in the field of a person's re-identification research are characteristic representations that are easily affected by closure (abhorrent to other objects). Furthermore, after extracting local features by means of a boundary box, the background image still contains and does not focus on the human body parts. This study comes up with a method combination of CNN, SVM classification, and semantic segmentation. CMC (Cumulative Matching Characteristics) and mAP (mean Average Precision) are measurements of assessment that will be utilized to measure the operation of re-identification. The ResNet + SVM + SSP-ReID technique performed best in the Market dataset, with a CMC increase of 3-10% (rank-1 through rank-20). The Market and CUHK03 (D) datasets both showed improvements of 1-4.1% in mAP. Keywords Person re-identification; Feature extraction; CNN; SVM; Semantic segmentation;